Development of Worksheet Based on The Local Wisdom of Samaturu for The Environmental Pollution Module In SMA Negeri 1 Mowewe - Ulmayani Ulmayani; A. S. Alonemarera; Saparuddin Saparudin (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2026)
Background: Learning in the Merdeka Curriculum emphasizes the integration of local wisdom to create more contextual learning experiences. However, environmental pollution topics are still often taught theoretically, resulting in students having limited understanding of their practical application and low environmental awareness. Observations and questionnaire results at SMA Negeri 1 Mowewe Senior High School revealed that 90.6% of students needed learning materials that could foster environmental awareness. Therefore, a Student Worksheet based on the local wisdom values of Samaturu was developed. Methodology: This study employed a Research and Development (R&D) approach using the ADDIE model. Data were collected through interviews, student needs questionnaires, expert validation, and teacher and student response questionnaires. The effectiveness of the Student Worksheet was evaluated using a one-group pretest-posttest design by measuring students’ Samaturu attitudes based on the indicators of cooperation, mutual assistance, responsibility, and participation. Findings: The developed Student Worksheet obtained a validity index of 82.72%, which was categorized as highly valid according to the validity criteria used in this study. Its practicality level reached 91.46%, which was categorized as highly practical based on the practicality criteria applied. Descriptive analysis showed that the average students’ Samaturu attitude score increased from 42.48 to 88.31 after the implementation of the Student Worksheet. Furthermore, the Wilcoxon Signed-Rank Test yielded a significance value of 0.000 (< 0.05), indicating that the Samaturu local wisdom-based Student Worksheet was effective in improving students’ Samaturu attitudes in environmental pollution learning. Contribution: The Samaturu local wisdom-based Student Worksheet is feasible for use as a contextual teaching material in biology learning. The integration of Samaturu values into learning activities contributes to fostering students’ cooperation, environmental awareness, and responsibility toward the environment